Development of an ORMAWA Work Program Management Information System Using a User-Centered Design Approach - Muhammad Helmi; Mohammad Reza Faisal; Friska Abadi; Dodon Turianto Nugrahadi; Setyo Wahyu Saputro; Deni Sutaji (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2026)
Student organizations (ORMAWA) at the Faculty of Mathematics and Natural Sciences, Universitas Lambung Mangkurat, face significant challenges in managing their work programs manually. This reliance on paper-based processes and decentralized record-keeping leads to chronic delays, documentation errors, and difficulties in tracking accountability. These issues severely hamper efficient coordination with faculty administrators, complicating timely decision-making and budget monitoring. The primary aim of this research is to develop and implement a web-based work program management information system for ORMAWA using a User-Centered Design (UCD) approach. Specific objectives include providing a centralized digital platform for program submission, approval, and reporting, and significantly enhancing the administrative efficiency and accountability of the entire workflow. The research methodology involved requirements gathering, iterative system design, and implementation using the React JS and Laravel frameworks. Evaluation was conducted through black box testing and User Acceptance Testing (UAT) with 13 ORMAWA administrators. Results demonstrate high user satisfaction (85%) and a substantial 30% efficiency improvement in program submission and reporting processes. The UCD approach was crucial in delivering a system that successfully eliminated redundant administrative tasks and centralized documentation. This study contributes to the application of UCD in developing organizational management systems in higher education, demonstrating how technology can transform traditional administrative workflow.